Discrete-Time Finite Horizon Approximation of Infinite Horizon Optimization Problems with Steady-State Invariance - Mercenier, Jean; Michel, Philippe (Econometrica, 1994)
Jean Mercenier, Philippe Michel, Discrete-Time Finite Horizon Approximation of Infinite Horizon Optimization Problems with Steady-State Invariance, Econometrica, Vol. 62, No. 3 (May, 1994), pp. 635-656